A1.1 Identification and phenotyping of innate lymphoid cells present in the diseased joints of patients with spondyloarthritis, rheumatoid arthritis and psoriatic arthritis. (13th February 2015) - Al-Mossawi, MH; De Wit, J; Kendrick, B; Gundle, R; Bowness, P
Abstract : Background and aims: Innate lymphoid cells (ILCs) have been recently identified at a number of different tissues and are thought to be an important class of innate immune cells involved in the initiation of the inflammatory response during health and disease. It is not known whether these cells exist in the human joint. We set out to identify and characterise these cells in the joints of patients with inflammatory arthritis. Methods: Matched synovial fluid and peripheral blood mononuclear cells from patients with spondyloarthritis (SpA) and psoriatic arthritis (PsA) were isolated and phenotyped using flow cytometry. In addition, cells from explanted orthopaedic surgical tissue samples were obtained from patients with SpA, PsA and rheumatoid arthritis (RA) and cultured in media containing interleukin-2 and interleukin-7. Intracellular cytokine staining was performed and analysed by flow cytometry. Results: A population of lineage-negative (i.e. negative for CD3, CD5 CD8, CD11b, CD11c, CD14, CD19, CD20, CD34, TCR-γδ) CD45 positive, IL-7R positive cells was identified in the synovial fluid and tissue of diseased human joints. Further phenotyping showed these to be either C-KIT positive ILC3 cells or C-KIT negative ILC1 cells. CRTH2 positive ILC2 cells were not detected. Comparison of matched blood and synovial fluid cells showed ILC3 populations were enriched in the joint and expressed HLA-DR. Discussion and conclusions: ILC populations (type 1 and type 3) are pre present in the synovial fluid and synovial tissue of inflamed SpA, PsA and RA joints. These cells are capable of rapid cytokine release and are potentially highly inflammatory. They may also play a role in antigen presentation through HLA-DR expression. Understanding the role of ILCs in health and disease is important for deciphering the processes taking part in early SpA pathogenesis.